PENGARUH PEMBERIAN MADU HUTAN TERHADAP PROLIFERASI LIMFOSIT PADA HEWAN UJI TIKUS JANTAN GALUR WISTAR - Kartika Sari Senas; Yunita Linawati (Sanata Dharma University, 2012)
Abstract: Forest honey is produced by wild bees by taking nectars from several kinds of plant.One of active chemicals contained within honey is flavonoid. It is believed as animmunomodulator due to it has role in fighting against free radicals and increasing body immunesystem against disease infection. This research aimed to understand the influences of foresthoney administration to the lymphocyte proliferation on male mice Wistar family. This researchis a pure, experimental with one way, random research design. Total of 20 rats was divided into 4groups. Each group was given honey forest with dose of 0,27; 0.54; 1.08 mL/200 g BW, andnegative control group was given aquadest 2.5 mL/200 g BW. The lymphocyte proliferation ismeasured from the amount of lymphocyte based on Optical Density (OD) values, the read onELISA reader at the wavelength of 550 nm. The result shown that the administration of foresthoney has effect on significance increase the lymphocyte proliferation (p0.05) than negativecontrol on male mice Wistar family.Key words : Foresthoney, lymphocyte proliferation, immunomodulator